SP0181 Chronic Pain Control - Experience of A Portuguese Patient Group Initiative. (15th July 2016) - Marques, C.S.
Abstract : The Patient Group of Chronic Pain (Núcleo da Dor) of the LPCDR - Portuguese League Against Rheumatic Diseases (which also has Osteoarthritis, Sjögren Syndrome and Scleroderma patients' groups), was born in 2014 and is centred in the chronic pain associated to rheumatic diseases. Its primary mission is to make this health condition VISIBLE to other people and to support the improvement of quality of life of all patients suffering from this pathology (about 30% of Portuguese people). The Patient Group of Chronic Pain (ND) is a participatory group that wants to share experiences, learn and implement coping strategies, with a positive, global, ecological and effective attitude. Besides the central role of the rheumatologist (an ally in pain reduction, disease control and treatment compliance), the support of all health professionals, family and friends, we know that the main role belongs to the patient as an expert of his body, and he's also the first to be involved in adapting daily life to new needs, difficulties and constraints. Each day with chronic pain is an emotional, functional and behavioural challenge that requires enhanced skills. Therefore, we believe that we do not choose to be sick, but we can choose to live better - with well-being and dignity - and that is in our hands to act and control the impact of pain on daily life. That's why ND is committed to: Sharing experiences and self-effective strategies; Learning to live with pain; Reducing disturbances associated to pain experience; Informing, raising public awareness and call to action; Being committed to an effective treatment, therapeutic and additional activities; Capitalizing positive synergies; Identifying scientific, therapeutic, recreational, behavioural approaches; Preserving the dignity and the patient's well-being; Taking responsibility in pain's self-control; Defining priorities and reset beliefs, values, attitudes, behavior and skills (coping) … and believing in the social responsibility of patients for a sustainable health. How? Among other activities and events already developed, we launched a National Photography Contest "Chronicles of Paint" which was one of our starting points. It was an opportunity to raise awareness on the invisibility of pain while generating artistic products with powerful visual messages. As a result, the selected photographs provided us material for exhibitions, enabling us to reach out to different audiences. The "Chronicles of Pain" were exhibited at FNAC Alfragide Shopping Centre, at the National Association of Pharmacies and at the Rectory of the New University of Lisbon. We have also presented a poster about this initiative at the Annual Conference of PARE in Zagreb (2014). In 2015, the selected photos were published in the book commemorating the 33rd anniversary of LPCDR, "Turn the Page", along with 33 texts received for Edgar Stene Prize (2005–2014). We have analysed the submitted photographs and the underlying perceptions of pain and suffering traduced in the visual snapshot, since the goal of the contest was to associate an image to pain. We have also analysed the preferences of a specific public, more closely related with rheumatic and musculoskeletal diseases. The results provided us some guidance towards a communication strategy. Our Thematic Sessions also provided us some unmet needs that we are addressing, by developing larger projects (like POSSO - Oriented Program for Overcoming RMDs and Optimize Health) for a better management of pain and chronic conditions. We must do something to draw the attention, talk about it, and call to action to reduce this PAIN scourge. There is no time to loose … don't you agree? Disclosure of Interest: None declared